An Experimental Study of Wave Impact Loads on an FPSO Bow in 2D Wave-Tank - Dong-Min Park; Byoungjae Park; Kangsu Lee (한국해양공학회지, 2024)
In harsh environments, an floating production storage and offloading (FPSO) is occasionally damaged by impact loads, such as bow flare slamming and green water. This study conducted an impact load measurement experiment on a model of an FPSO bow in a 2D wave tank. Three types of frequency-focused waves (steep, spilling, and plunging) were generated, and the speed and slope of the waves were measured. Seven wave probes were placed in a row, and the wave elevation was measured to determine the speed and slope of the waves. In addition, the side of the 2D wave tank was photographed with a high-speed camera. The speed and slope of the waves obtained from the wave probe array agreed well with those obtained from the photographs taken using a high-speed camera. In the case of a steep wave, wave runup occurred at the bow before the wave reached the bow of the FPSO, so no impact load was generated, and only hydrostatic pressure was measured. Impact loads were generated in the spilling and plunging waves, and the magnitude of impact loads using the Von Karman’s estimation formula and the impact loads measured in model tests showed similar values.